How time exposure, role engagement and task essence ("3E") of volunteering interact to associate with healthy aging: a cross-sectional mixed-method study in Hong Kong. - Lu, Shiyu (Journals of Gerontology Series B: Psychological Sciences & Social Sciences, 2026)
Objectives This study introduces the 3E framework of volunteering, including time exposure (e.g. volunteering hours), role engagement, and task essence (e.g. types of activities) and investigates how these dimensions and their interactions impact healthy aging outcomes in older adults. Methods A mixed-methods cross-sectional study using purposive sampling was conducted in social care units with 457 participants aged 60 and older who volunteered at least one hour in the past year in Hong Kong (2024–2025), in addition to seven focus groups involving 46 older adults. Role engagement in volunteering was assessed using the adapted Chinese version of the Utrecht Work Engagement Scale. Results Role engagement (β = 0.92, p  < .001), emotional support tasks (β = 1.35, p =.022), and creative activities (β = 1.09, p  = .018) were positively associated with subjective well-being (SWB). Creative activities were linked to better self-rated health, while time exposure was associated with improved cognition. Role engagement amplified the health benefits of both time exposure and task nature. A three-way interaction among role engagement, time exposure, and creative tasks was significantly associated with better SWB (β = 0.66, p =.026) and lower depressive symptoms (β = −0.39, p =.027). Qualitative findings revealed that role engagement in late-life volunteering unfolds through four themes: role internalization, mental resilience, cognitive investment, and meaning-making. Discussion This study validates the 3E framework, demonstrating that role engagement optimizes the health benefits of late-life volunteering hours and volunteering types. Policymakers should transition from focusing solely on volunteering quantity to adopting a holistic approach that optimizes healthy-aging benefits of late-life volunteering.